The main defense mechanisms found in obsessive neurosis: A look at the formation of symptoms - Scatolin, Henrique Guilherme (Revista de Psicologia, 2013)
This article intends to focus the main defense mechanisms found in obsessive neurosis, such as displacement, reaction formation, isolation and annulment. To develop this discussion, part of a reassessment of the pre-psychoanalytic work to Inhibitions, Symptoms and Anxiety published in 1926, focusing on this understanding the Freud’s idea of the symptom and the main defense mechanisms present in this neurosis. It concludes that for a better understanding of the etiology symptomatic neurosis, it is necessary to examine each mechanism in its particularity, since it expresses the uniqueness of each symptom in its essence. These defense mechanisms can be regarded as a mask to cover up the symptoms, but to conceal, reveal all repressed desires, denoting the unique history of each patient.